Surgical-Based Classification for Microtia. Issue 6 (September 2018) - Campo, Armando Apellaniz; Victor-Baldin, André; Contreras-Mérida, Sara M.
Abstract : Abstract: The known classifications for microtia have been cumbersome and difficult to apply in daily consultation. The lack of a progressive surgical behavior according to each degree of affection also contributes to confusion and in a lower success rate in clinical application. The authors propose a progressive surgical classification that takes into consideration the principal anatomical defect and the corresponding correction with modern techniques, having eliminated from previous classifications, those elements that are now considered deformations of the ear, capable of conservative treatment in early stages of life.